The effect of free cash flow and ownership structure on dividend payout ratio in manufacturing companies in Indonesia - Afandi Suhartono (Universitas Hayam Wuruk Perbanas, 2015)
Dividend policy is used to determine the amount of net profit after tax that will be distributed to shareholders and the amount of equity in the net income that will be used to finance the company's investment. Optimal dividend policy is a dividend policy that creates a balance between current dividends and growth in the future to maximize the company's stock price. The purpose of this study is to analyze the effect of Free Cash Flow (FCF) and Ownership Structure, consisting of Institutional Own-ership, Family Ownership and Foreign Ownership, on Dividend Payout Ratio (DPR) in manufacturing companies listed on the Indonesia Stock Exchange in 2011-2013. The research methodology used is descriptive analysis method and statistical analysis method. The data used is secondary data consisting of 173 research data used as the sample. Hypothesis testing is done by using multiple linear regression analysis. The results of regression analysis show that free cash flow, family ownership and foreign ownership have positive effect on dividend payout ratio, while institutional ownership does not have negative effect on dividend payout ratio.